A Nurse-Directed Model for Nitrous Oxide Use During Labor. Issue 3 (May 2017) - Pinyan, Toni; Curlee, Kelly; Keever, Mellanie; Baldwin, Kathleen M.
Abstract: Background: Nitrous oxide has a long history of use and has been well documented in the literature as a safe, effective, and inexpensive option for pain management in labor in other countries, but it is underused in the United States. Local Problem: Pain relief options for laboring women in rural community hospitals with a small perinatal service are limited due to lack of availability of in-house anesthesia coverage. Method: This quality improvement project involved development and implementation of a nurse-driven, self-administered, demand-flow nitrous oxide program as an option for pain relief for laboring women in a rural community hospital. Intervention: Women's Services registered nurses developed the project using an interdisciplinary team approach based on an extensive literature review and consultation with experts across the country. The hospital is part of a large healthcare system; approval was sought and obtained by the system as part of the project. Cost analysis and patient satisfaction data were evaluated. Outcomes were monitored. Results: Approximately one half of the patients who have given birth at the hospital since initiation of the project have used nitrous oxide during labor. The majority of women who participated in a survey after birth found it helpful during mild-to-moderate labor pain. No adverse effects have noted in either the mother or the baby following nitrous oxide use. Clinical Implications: Initiation and management of nitrous oxide by registered nurses is a safe and cost-effective option for labor pain. It may be especially beneficial in hospitals that do not have 24/7 in-house anesthesia coverage. Abstract : Nitrous oxide is becoming more widely available to women laboring and giving birth in the United States. A nurse-directed model for offering nitrous oxide during labor in a small volume perinatal service in a rural community hospital is presented.